A sludge treatment process for a sewage treatment plant

CN120208500BActive Publication Date: 2026-10-16CHINA CONSTRUCTION EIGHTH BUREAU (INNER MONGOLIA) CONSTRUCTION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510492379.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-18
Publication Date
2026-10-16
Estimated Expiration
2045-04-18

AI Technical Summary

Technical Problem

[0003]但是传统污泥处理工艺中电子传递速率受限,缺乏高效导电介质,导致甲烷产率低、消化周期长,且易产生硫化氢等副产物,需额外脱硫处理,同时现有导电材料成本高昂且难以回收,废弃后易造成环境负担;化学药剂过量投加导致污泥盐分累积,影响后续资源化利用

Benefits of technology

[0026] 1. In this invention, biochar serves as the core medium, directly participating in the construction of the structure. Its porous characteristics and adsorption properties are integrated into the filter interlayer and ecological slope protection of the hydraulic structure, replacing traditional sand filter media and concrete additives. This simplifies the construction process and enhances structural functionality. The process equipment and building space are designed collaboratively. The guide walls of the anaerobic reactor and the refractory lining of the pyrolysis furnace are integrated and cast using biochar-based materials, significantly improving the matching accuracy between the equipment foundation and the main structure. The intelligent pre-embedded system embedded during construction allows the sensor network and process pipelines to be precisely positioned during the concrete pouring stage, effectively avoiding structural damage caused by later excavation and demolition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120208500B_ABST
    Figure CN120208500B_ABST
Patent Text Reader

Abstract

The application discloses a sludge treatment process for a sewage treatment plant. In the application, the sludge treatment process belongs to the technical field of civil engineering sludge treatment, and through multi-stage cooperation and resource closed loop design, dual breakthroughs of environmental benefits and economic benefits are realized. The synergistic effect of the biochar loaded nanomaterial significantly improves the organic matter decomposition efficiency, and the unique conductive network structure accelerates the electron transfer in the anaerobic digestion process, so that the methane generation rate breaks through the bottleneck of the traditional process. The biochar as the core medium directly participates in the construction of the structure body, and the porous characteristics and adsorption performance of the biochar are integrated into the filter interlayer and the ecological revetment of the hydraulic structure, replacing the traditional sand filter material and the concrete additive, so that the construction process is simplified and the structural functionality is enhanced. The process equipment and the building space adopt the cooperative design principle, the guide wall of the anaerobic reactor and the refractory lining of the pyrolysis furnace are integrally poured by combining the characteristics of the biochar-based material, and the matching precision of the equipment foundation and the main structure is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of civil engineering sludge treatment technology, specifically a sludge treatment process for sewage treatment plants. Background Technology

[0002] Sludge treatment is a crucial step in urban wastewater treatment, involving the reduction, stabilization, and resource recovery of sludge generated after wastewater treatment. It mainly includes steps such as sludge thickening, sludge dewatering, sludge digestion, sludge drying, and sludge incineration. Sludge thickening reduces the water content of the sludge through physical methods, increasing its concentration; dewatering further removes water, significantly reducing its volume; digestion utilizes microorganisms to decompose organic matter in the sludge, achieving stabilization; drying and incineration reduce sludge volume and eliminate pathogens through reducing moisture and high-temperature combustion, respectively, achieving resource recovery and harmlessness. Sludge treatment not only helps improve environmental quality but also recovers resources, contributing to sustainable development.

[0003] However, traditional sludge treatment processes have limited electron transfer rates and lack efficient conductive media, resulting in low methane yields, long digestion cycles, and the easy generation of byproducts such as hydrogen sulfide, requiring additional desulfurization treatment. At the same time, existing conductive materials are expensive and difficult to recycle, and their disposal can easily cause environmental burden. Excessive addition of chemical agents leads to the accumulation of sludge salts, affecting subsequent resource utilization. Summary of the Invention

[0004] The purpose of this invention is to provide a sludge treatment process for wastewater treatment plants in order to solve the problems mentioned above.

[0005] The technical solution adopted in this invention is as follows: a sludge treatment process for a wastewater treatment plant, the process comprising the following steps:

[0006] S1: Civil engineering reinforced concrete ultrasonic tank body, pre-embedded galvanized steel pipe conduit, installation of 316L stainless steel vibrating plate base, and integrated CPVC calcium peroxide dosing pipeline system on the tank top.

[0007] S2: Construct the civil engineering structure of a two-phase anaerobic reactor with an internal biochar conductive dielectric layer;

[0008] S3: Construct a microwave hydrolysis reaction tank and pre-bury the supporting volatile fatty acid recovery pipeline;

[0009] S4: Civil engineering solar greenhouse drying workshop, with MOF material adsorption layer embedded in the wall surface;

[0010] S5: Casting the structure of the oxygen-deficient pyrolysis kiln body, and matching the pyrolysis gas catalytic reforming reuse pipeline network;

[0011] S6: Construct an acid leaching reaction tank and crystallization device, using a biochar magnesium source carrier structure;

[0012] S7: Civil engineering biological filter tower base, with activated carbon adsorption unit and CO capture pipeline installed;

[0013] S8: Embed a network of sensors for monitoring process parameters and deploy a digital twin control system;

[0014] S9: Implement full-chain civil engineering renovation: secondary sedimentation tank with embedded biochar filter interlayer; stainless steel grid anchored concrete; rain garden with layered backfill of biochar planting soil; geotextile wrapped with biochar adsorption layer at the bottom of municipal pipe trench, and set up detachable inspection well structure.

[0015] In a preferred embodiment, in step S1, concentrated sludge from a wastewater treatment plant, with an initial moisture content controlled at 95%–97%, is first treated in a high-frequency ultrasonic reactor with a frequency of 20–40 kHz. The ultrasonic power density is set to 0.5 watts per milliliter, and the treatment time is 30 minutes. The sludge temperature is maintained below 35 degrees Celsius to prevent pyrolysis of organic matter. After treatment, 5 grams of calcium peroxide powder are added per liter of sludge, and the mixture is stirred at 200 rpm for 20 minutes to ensure uniform dispersion of calcium peroxide and release of active oxygen, simultaneously completing cell wall disruption, heavy metal passivation, and pathogenic microorganism inactivation.

[0016] In a preferred embodiment, in step S2, the biochar-supported nanomaterials include: 60-70 parts by weight of sludge-based biochar, 10-15 parts by weight of polydopamine-coated nano-zero-valent iron, 8-10 parts by weight of conductive polyaniline, 5-8 parts by weight of superparamagnetic Fe3O4, 3-5 parts by weight of diammonium hydrogen phosphate, 2-3 parts by weight of calcium carbonate, and 1-2 parts by weight of KOH activator.

[0017] The preparation method of the biochar-supported nanomaterials includes: firstly, taking dewatered sludge from a wastewater treatment plant, subjecting it to a step-by-step pyrolysis process, followed by pre-carbonization at 300℃ for 30 minutes and activation at 600℃. During the activation stage, KOH is used for impregnation at a mass ratio of 1:2, and the mixture is kept at this temperature for 1 hour under nitrogen protection. Subsequently, ash is removed by acid washing with 0.1M HCl, followed by washing with deionized water, vacuum drying, and grinding to 200 mesh to obtain sludge-based biochar. Next, the biochar is soaked in a 0.5M FeSO4 solution at a solid-liquid ratio of 1:10, ultrasonically dispersed for 30 minutes, and then 0.5M FeSO4 solution is added dropwise. NaBH4 solution was used to generate nano-zero valent iron by controlling the molar ratio of Fe2+ to BH4- at 1:2 under nitrogen protection for 2 hours. Then, aniline monomer with a mass ratio of 1:5 to biochar was added, and in-situ polymerization was carried out using ammonium persulfate as an initiator to form a polyaniline conductive coating layer. Finally, FeCl2·4H2O and FeCl3·6H2O were dissolved in a 1:2 molar ratio by co-precipitation, and ammonia was added dropwise to adjust the pH to 10. Fe3O4 magnetic particles were prepared by stirring at 60°C for 1 hour. The particles were then separated and loaded onto the surface of biochar by magnetic field separation, and then mixed with diammonium hydrogen phosphate and calcium carbonate by ball milling at 300 rpm for 2 hours. Finally, the mixture was pressed into tablets and granulated to obtain the finished biochar-supported nanomaterials with a particle size of 2-3 mm.

[0018] In a preferred embodiment, in step S3, the anaerobic digestion residue is dewatered to a moisture content of 80% using a plate and frame filter press, and then fed into a microwave-assisted hot hydrolysis reactor. The reaction conditions are set to a microwave power of 800 watts, a heating rate of 10 degrees Celsius per minute, a target temperature of 160 degrees Celsius maintained for 30 minutes, and a reaction pressure stabilized at 6 bar via an automatic pressure relief valve. The hydrolyzed material is discharged via a screw conveyor, and polyaluminum chloride is added as a conditioning agent at a dosage of 5% of the dry sludge mass. After a second dewatering process using a belt filter press, the moisture content is reduced to below 60%, and the sludge resistivity is reduced to 1.0 × 10^12 m / kg.

[0019] In a preferred embodiment, in step S4, the dewatered sludge is transported to a double-layered solar greenhouse with a light transmittance of 92%. The top of the greenhouse is covered with a phase change heat storage material, and the bottom is laid with a breathable and impermeable membrane. During the day, the temperature is raised to 50-60 degrees Celsius using solar radiation, and at night, a heat pump is activated to maintain the temperature at 40 degrees Celsius. The sludge is continuously dried for 72 hours until the moisture content is reduced to 65%. Subsequently, a hydrophobic metal-organic framework adsorption bed is used for deep dewatering.

[0020] In a preferred embodiment, in step S5, the dewatered sludge enters a rotary pyrolysis furnace and is heated in three stages under a nitrogen atmosphere: the first stage heats up to 300 degrees Celsius at a rate of 15 degrees Celsius per minute, with a residence time of 30 minutes to achieve preliminary cracking of organic matter; the second stage heats up to 500 degrees Celsius, with a residence time of 45 minutes to complete secondary cracking of tar; the third stage heats up to 700 degrees Celsius and holds at that temperature for 60 minutes to generate biochar with a specific surface area greater than 500 square meters per gram. The pyrolysis gas, after dust removal by a cyclone separator, enters a catalytic reforming tower, where it is reformed into syngas at 850 degrees Celsius using a nickel-based catalyst.

[0021] In a preferred embodiment, in step S6, the pyrolysis ash is pulverized to 100 mesh using a ball mill, and a 1 mol / L sulfuric acid solution is added at a solid-liquid ratio of 1:10. The mixture is then stirred and leached at 80°C for 2 hours, resulting in a phosphorus leaching rate exceeding 90%. After adjusting the pH of the leachate to 9.0, biochar-loaded magnesium chloride is added, reacting to form struvite crystals. These crystals are then centrifuged, washed with pure water, and yielded magnesium ammonium phosphate with a purity >95%. This is further calcined at 450°C for 2 hours.

[0022] In a preferred embodiment, in step S7, the pyrolysis tail gas, after passing through a bag filter, enters a two-stage biological filter tower: the first stage is filled with sulfur-oxidizing bacteria biological packing material, with an empty tower residence time of 40 seconds and a hydrogen sulfide removal efficiency >98%; the second stage is filled with nitrifying bacteria biofilm, with the spray liquid pH controlled at 7.5-8.0 and an ammonia nitrogen removal rate >90%. The purified tail gas is then passed into an amino-functionalized silica gel adsorption tower, with an adsorbent bulk density of 600 kg / m³, selectively capturing carbon dioxide at 50°C. After adsorption saturation, it is desorbed by steam at 120°C, with a carbon dioxide purity >99%, and then liquefied and stored after being pressurized to 30 bar.

[0023] In a preferred embodiment, in step S8, a digital twin system is deployed to collect real-time data from 12 types of sensors, including sludge flow rate, temperature, pH, ORP, and volatile fatty acids, updating the database every 5 seconds. A multivariate prediction model is established using a long short-term memory neural network, with an input layer containing 32 neurons, a hidden layer with 64 nodes, and an output layer that dynamically optimizes 18 process parameters, including ultrasonic power, pyrolysis temperature, and MOF adsorption cycle.

[0024] In a preferred embodiment, in step S9, the prepared biochar is added at a ratio of 20 grams per ton of wastewater to the advanced treatment unit after the secondary sedimentation tank, achieving a total phosphorus adsorption capacity of 35 mg / g, replacing 80% of the traditional polyferric sulfate reagent usage. Hydroxyapatite slow-release fertilizer is evenly spread using municipal greening fertilizer trucks, with an annual application rate of 5 kg per acre, increasing the available phosphorus content in the soil by 2.3 times. The final effluent quality of the system meets the requirements of chemical oxygen demand ≤30 mg / L and total phosphorus ≤0.3 mg / L. The carbon footprint of the entire sludge treatment process is calculated to reduce emissions by 1.5 kg of carbon dioxide equivalent per ton of dry sludge.

[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0026] 1. In this invention, biochar serves as the core medium, directly participating in the construction of the structure. Its porous characteristics and adsorption properties are integrated into the filter interlayer and ecological slope protection of the hydraulic structure, replacing traditional sand filter media and concrete additives. This simplifies the construction process and enhances structural functionality. The process equipment and building space are designed collaboratively. The guide walls of the anaerobic reactor and the refractory lining of the pyrolysis furnace are integrated and cast using biochar-based materials, significantly improving the matching accuracy between the equipment foundation and the main structure. The intelligent pre-embedded system embedded during construction allows the sensor network and process pipelines to be precisely positioned during the concrete pouring stage, effectively avoiding structural damage caused by later excavation and demolition.

[0027] 2. In this invention, a biochar-based deep phosphorus removal unit replaces traditional chemical agents, reducing the risk of secondary pollution. The recovered phosphorus resources are modified and transformed into a slow-release soil conditioner, simultaneously solving the dual problems of phosphorus removal costs in wastewater treatment plants and phosphorus deficiency in urban greening. Solar-coupled adsorption dehydration technology overcomes the high energy consumption limitations of traditional thermal drying, and combined with an intelligent control system, achieves refined management of the dehydration process. The final product chain encompasses various high-value products such as energy gases, carbon-based materials, and slow-release fertilizers, forming a closed-loop model of "treatment-reuse-feedback," which not only reduces the overall cost of sludge disposal but also extends derivative values ​​such as ecological restoration and carbon sequestration enhancement, endowing wastewater treatment plants with sustainable operation capabilities. Attached Figure Description

[0028] Figure 1 This is a schematic diagram illustrating the process principle of the present invention. Detailed Implementation

[0029] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0030] Example 1:

[0031] Reference Figure 1 ,

[0032] A sludge treatment process for a wastewater treatment plant, comprising the following steps:

[0033] S1: When physically breaking down concentrated sludge using high-frequency ultrasound, a dedicated ultrasonic tank structure is designed: a 316L stainless steel vibrating plate base is installed in the reinforced concrete tank, and high-frequency power is stably transmitted through pre-embedded galvanized steel conduit. The amplitude of the vibrating plate is controlled at 50-70μm to optimize cell wall breaking efficiency. Simultaneously, a calcium peroxide dosing system is integrated at the top of the tank, using corrosion-resistant CPVC pipes connected to an explosion-proof metering pump. A ring-shaped dosing device is used to achieve 360° mixing of the agent and sludge.

[0034] S2: Ultrasonic-treated sludge was mixed with kitchen waste, and biochar-supported nanomaterials were added as a conductive medium to construct a direct interspecies electron transport (DIET) system. A two-phase anaerobic reactor (acid-producing phase → methanogenic phase) was used, which increased methane yield by 30% and shortened the digestion cycle to 12 days.

[0035] S3: Microwave-assisted hot water hydrolysis (temperature 160℃, pressure 6 bar, microwave power 800W) is used to decompose lignin and other recalcitrant organic matter, improving dewatering performance by 40%. Volatile fatty acids (VFAs) are recovered simultaneously for carbon source replenishment in the wastewater treatment plant.

[0036] S4: A solar greenhouse drying system (integrated phase change thermal storage material) is used for initial dehydration, combined with a new type of hydrophobic MOF material to adsorb water, reducing the sludge moisture content from 80% to 55%, and reducing energy consumption by 70% compared with traditional thermal drying.

[0037] S5: Dewatered sludge undergoes staged pyrolysis (300℃→500℃→700℃) under anoxic conditions to generate high specific surface area biochar (>500m²). 2 / g). The pyrolysis gas is catalytically reformed and reused as a heat source for the system, achieving energy self-circulation;

[0038] S6: Phosphorus is recovered from pyrolysis ash via acid leaching (H2SO4)-struvite crystallization, using biochar as a magnesium source carrier, achieving a phosphorus recovery rate >85%. The recovered phosphorus product is modified with hydroxyapatite to prepare a slow-release soil conditioner.

[0039] S7: The integrated biological filter tower (sulfur oxidation / nitrifying bacteria) and activated carbon adsorption device treat pyrolysis tail gas. It uses amino-functionalized silica gel to capture CO and convert it into bicarbonate, achieving carbon sequestration and odor removal rate >95%.

[0040] S8: Deploy a digital twin system to monitor data in real time through online sensors and combine it with an LSTM neural network to predict the optimal process parameters (such as ultrasonic intensity and pyrolysis temperature) and dynamically adjust the equipment's operating status.

[0041] S9: High specific surface area biochar produced by pyrolysis is integrated as a functional material into the civil engineering renovation of sewage treatment plants. Biochar filter interlayers are embedded in the side walls of the secondary sedimentation tank effluent channel, and carbon-based fillers are fixed with stainless steel grid frames and reliably connected to the concrete structure by bolt anchoring. Simultaneously, 30% biochar is added to the planting soil during the construction of the plant's rain garden. After layered backfilling and compaction, a permeable concrete surface layer is laid to form an ecological filter bed with nitrogen and phosphorus removal functions. When pre-burying slow-release phosphate fertilizer transmission pipelines in municipal green belts, a biochar adsorption layer is laid at the bottom of the trench to intercept runoff pollutants. Geotextile is used to wrap the carbon particles to prevent loss, and detachable inspection wells are set at the pipe joints to facilitate the replacement and maintenance of the carbon layer, realizing the full-chain circulation of carbon-based materials from sewage treatment to municipal engineering.

[0042] In step S1, concentrated sludge from a wastewater treatment plant, with an initial moisture content controlled at 95%–97%, is first treated in a high-frequency ultrasonic reactor at a frequency of 20–40 kHz. The ultrasonic power density is set to 0.5 watts per milliliter, and the treatment time is 30 minutes. The sludge temperature is maintained below 35 degrees Celsius to prevent pyrolysis of organic matter. After treatment, 5 grams of calcium peroxide powder are added per liter of sludge, and the mixture is stirred at 200 rpm for 20 minutes to ensure uniform dispersion of calcium peroxide and release of active oxygen, simultaneously completing cell wall disruption, heavy metal passivation, and pathogen inactivation. The dissolved chemical oxygen demand (SCOD) of the pretreated sludge is increased to more than 2.3 times that of the original sludge, and the volatile solids (VS) degradation rate is less than 8%.

[0043] In step S2, the biochar-supported nanomaterials include: 60 parts by weight of sludge-based biochar, 10 parts by weight of polydopamine-coated nano-zero-valent iron, 8 parts by weight of conductive polyaniline, 5 parts by weight of superparamagnetic Fe3O4, 3 parts by weight of diammonium hydrogen phosphate, 2 parts by weight of calcium carbonate, and 1 part by weight of KOH activator.

[0044] The preparation method of biochar-supported nanomaterials includes: firstly, dewatered sludge from a wastewater treatment plant is taken and subjected to a stepped pyrolysis process, followed by pre-carbonization at 300℃ for 30 minutes and activation at 600℃. During the activation stage, KOH is used for impregnation at a mass ratio of 1:2, and the mixture is kept at this temperature for 1 hour under nitrogen protection. Subsequently, ash is removed by acid washing with 0.1M HCl, followed by washing with deionized water, vacuum drying, and grinding to 200 mesh to obtain sludge-based biochar. Next, the biochar is soaked in 0.5M FeSO4 solution at a solid-liquid ratio of 1:10, ultrasonically dispersed for 30 minutes, and then 0.5M FeSO4 solution is added dropwise. NaBH4 solution was used to generate nano-zero valent iron by controlling the molar ratio of Fe2+ to BH4- at 1:2 under nitrogen protection for 2 hours. Then, aniline monomer with a mass ratio of 1:5 to biochar was added, and in-situ polymerization was carried out using ammonium persulfate as an initiator to form a polyaniline conductive coating layer. Finally, FeCl2·4H2O and FeCl3·6H2O were dissolved in a 1:2 molar ratio by co-precipitation, and ammonia was added dropwise to adjust the pH to 10. Fe3O4 magnetic particles were prepared by stirring at 60°C for 1 hour. The particles were then separated and loaded onto the surface of biochar by magnetic field separation, and then mixed with diammonium hydrogen phosphate and calcium carbonate by ball milling at 300 rpm for 2 hours. Finally, the mixture was pressed into tablets and granulated to obtain the finished biochar-supported nanomaterials with a particle size of 2-3 mm.

[0045] In step S3, the anaerobic digestion residue is dewatered to 80% moisture content using a plate and frame filter press, and then fed into a microwave-assisted hot hydrolysis reactor. The reaction conditions are set to a microwave power of 800 watts, a heating rate of 10 degrees Celsius per minute, a target temperature of 160 degrees Celsius maintained for 30 minutes, and a reaction pressure stabilized at 6 bar via an automatic pressure relief valve. The hydrolyzed material is discharged via a screw conveyor, and polyaluminum chloride (PAC) is added as a conditioner at a dosage of 5% of the dry sludge mass. After a second dewatering process using a belt filter press, the moisture content is reduced to below 60%, and the sludge resistivity is reduced to 1.0 × 10^12 m / kg. Simultaneously recovered volatile fatty acids are collected via a condenser at a concentration of 12,000 mg / L and directly reused as a carbon source for denitrification in the wastewater treatment plant.

[0046] In step S4, the dewatered sludge is transported to a double-layered solar greenhouse with 92% light transmittance. The top of the greenhouse is covered with a phase change thermal storage material (paraffin-expanded graphite composite material, phase change temperature 45 degrees Celsius), and the bottom is laid with a breathable and impermeable membrane. During the day, solar radiation is used to raise the temperature to 50-60 degrees Celsius, and at night, a heat pump is activated to maintain the temperature at 40 degrees Celsius. Continuous drying for 72 hours reduces the sludge moisture content to 65%. Subsequently, a hydrophobic metal-organic framework (MOF-303) adsorption bed is used for deep dewatering. The MOF material packing density is 200 kg per cubic meter, the adsorption cycle is 6 hours, and the final sludge moisture content is reduced to 55%, with a unit energy consumption of 0.6 kWh per ton of water evaporation.

[0047] In step S5, the dewatered sludge enters a rotary pyrolysis furnace and is heated in three stages under a nitrogen atmosphere: the first stage heats up to 300 degrees Celsius at a rate of 15 degrees Celsius per minute, with a residence time of 30 minutes to achieve initial cracking of organic matter; the second stage heats up to 500 degrees Celsius, with a residence time of 45 minutes to complete secondary cracking of tar; the third stage heats up to 700 degrees Celsius and holds at that temperature for 60 minutes to generate biochar with a specific surface area greater than 500 square meters per gram. The pyrolysis gas, after dust removal by a cyclone separator, enters a catalytic reforming tower, where it is reformed into syngas (H+CO ratio > 70%) at 850 degrees Celsius using a nickel-based catalyst. This syngas is then reused for combustion and heating in the pyrolysis furnace, achieving an energy self-sufficiency rate of 85%.

[0048] In step S6, the pyrolysis ash is pulverized to 100 mesh using a ball mill. A 1 mol / L sulfuric acid solution is added at a solid-liquid ratio of 1:10, and the mixture is stirred and leached at 80°C for 2 hours, achieving a phosphorus leaching rate exceeding 90%. After adjusting the pH of the leachate to 9.0, biochar-loaded magnesium chloride (MgCl₂·6H₂O to biochar mass ratio 1:5) is added, reacting to form struvite crystals. These crystals are then centrifuged, washed with pure water, and yielded magnesium ammonium phosphate with a purity >95%. Further calcination at 450°C for 2 hours converts it into hydroxyapatite slow-release fertilizer, with a phosphorus dissolution rate controlled below 5% within 24 hours.

[0049] In step S7, the pyrolysis tail gas, after passing through a bag filter, enters a two-stage biological filter tower: the first stage is filled with sulfur-oxidizing bacteria biological packing material, with an empty tower residence time of 40 seconds, achieving a hydrogen sulfide removal efficiency >98%; the second stage is filled with nitrifying bacteria biofilm, with the spray liquid pH controlled at 7.5-8.0, achieving an ammonia nitrogen removal rate >90%. The purified tail gas is then passed into an amino-functionalized silica gel adsorption tower, with an adsorbent bulk density of 600 kg / m³, selectively capturing carbon dioxide at 50°C. After adsorption saturation, it is desorbed by steam at 120°C, achieving a carbon dioxide purity >99%. The gas is then pressurized to 30 bar and liquefied for storage.

[0050] In step S8, a digital twin system is deployed to collect real-time data from 12 types of sensors, including sludge flow rate, temperature, pH, ORP, and volatile fatty acids, updating the database every 5 seconds. A multivariate prediction model is established using a Long Short-Term Memory (LSTM) neural network, with 32 neurons in the input layer, 64 nodes in the hidden layer, and the output layer dynamically optimizing 18 process parameters such as ultrasonic power, pyrolysis temperature, and MOF adsorption cycle. The system generates a global optimization scheme every 24 hours using a reinforcement learning algorithm, achieving equipment control response time of less than 1 second and reducing overall energy consumption by 12%.

[0051] In step S9, the prepared biochar is added at a ratio of 20 grams per ton of wastewater to the advanced treatment unit after the secondary sedimentation tank, achieving a total phosphorus adsorption capacity of 35 mg / g, replacing 80% of the traditional polyferric sulfate reagent usage. Hydroxyapatite slow-release fertilizer is evenly spread using municipal greening fertilizer trucks, with an annual application rate of 5 kg per acre, increasing the available phosphorus content in the soil by 2.3 times. The final effluent quality of the system meets the requirements of chemical oxygen demand (COD) ≤ 30 mg / L and total phosphorus ≤ 0.3 mg / L. The carbon footprint of the entire sludge treatment process is calculated to reduce emissions by 1.5 kg of carbon dioxide equivalent per ton of dry sludge.

[0052] From the above, we can conclude that:

[0053] In this invention, biochar serves as the core medium, directly participating in the construction of the structure. Its porous characteristics and adsorption properties are integrated into the filter interlayer and ecological slope protection of the hydraulic structure, replacing traditional sand filter media and concrete additives. This simplifies the construction process and enhances structural functionality. The process equipment and building space are designed collaboratively. The guide walls of the anaerobic reactor and the refractory lining of the pyrolysis furnace are integrated and cast using biochar-based materials, significantly improving the matching accuracy between the equipment foundation and the main structure. The intelligent pre-embedded system embedded during construction allows the sensor network and process pipelines to be precisely positioned during the concrete pouring stage, effectively avoiding structural damage caused by later excavation and demolition.

[0054] This invention achieves a dual breakthrough in environmental and economic benefits through multi-level synergy and resource closed-loop design. The synergistic effect of biochar-supported nanomaterials significantly improves the decomposition efficiency of organic matter. Its unique conductive network structure accelerates electron transfer during anaerobic digestion, enabling the methane generation rate to break through the bottleneck of traditional processes, while effectively inhibiting the generation of malodorous byproducts such as hydrogen sulfide. The superparamagnetic component endows the material with highly efficient recovery characteristics. Combined with a slow-release nutrient system, it significantly enhances microbial metabolic activity while reducing dependence on chemical agents, ensuring the stabilization of heavy metals and the inactivation of pathogens. The energy and material recycling design of each stage of the process converts sludge pyrolysis gas into a heat source for the system's own use, forming an internal energy circulation link and significantly reducing the demand for external energy input.

[0055] In this invention, a biochar-based deep phosphorus removal unit replaces traditional chemical agents, reducing the risk of secondary pollution. The recovered phosphorus resources are modified and transformed into a slow-release soil conditioner, simultaneously addressing the dual challenges of phosphorus removal costs in wastewater treatment plants and phosphorus deficiency in urban greening. Solar-coupled adsorption dehydration technology overcomes the high energy consumption limitations of traditional thermal drying, and combined with an intelligent control system, achieves refined management of the dehydration process. The final product chain encompasses various high-value products such as energy gases, carbon-based materials, and slow-release fertilizers, forming a closed-loop model of "treatment-reuse-feedback." This not only reduces the overall cost of sludge disposal but also extends into derivative values ​​such as ecological restoration and carbon sequestration enhancement, endowing wastewater treatment plants with sustainable operational capabilities.

[0056] Example 2:

[0057] Reference Figure 1 ,

[0058] A sludge treatment process for a wastewater treatment plant, comprising the following steps:

[0059] S1: High-frequency ultrasound is used to physically break down the concentrated sludge, disrupting the cell walls of microorganisms and releasing intracellular organic matter, thereby improving the efficiency of subsequent treatment. Calcium peroxide is added for chemical oxidation pretreatment, simultaneously achieving heavy metal passivation and pathogen inactivation.

[0060] S2: Ultrasonic-treated sludge was mixed with kitchen waste, and biochar-supported nanomaterials were added as a conductive medium to construct a direct interspecies electron transport (DIET) system. A two-phase anaerobic reactor (acid-producing phase → methanogenic phase) was used, which increased methane yield by 30% and shortened the digestion cycle to 12 days.

[0061] S3: Microwave-assisted hot water hydrolysis (temperature 160℃, pressure 6 bar, microwave power 800W) is used to decompose lignin and other recalcitrant organic matter, improving dewatering performance by 40%. Volatile fatty acids (VFAs) are recovered simultaneously for carbon source replenishment in the wastewater treatment plant.

[0062] S4: A solar greenhouse drying system (integrated phase change thermal storage material) is used for initial dehydration, combined with a new type of hydrophobic MOF material to adsorb water, reducing the sludge moisture content from 80% to 55%, and reducing energy consumption by 70% compared with traditional thermal drying.

[0063] S5: Dewatered sludge undergoes staged pyrolysis (300℃→500℃→700℃) under anoxic conditions to generate high specific surface area biochar (>500m²). 2 / g). The pyrolysis gas is catalytically reformed and reused as a heat source for the system, achieving energy self-circulation;

[0064] S6: Phosphorus is recovered from pyrolysis ash via acid leaching (H2SO4)-struvite crystallization, using biochar as a magnesium source carrier, achieving a phosphorus recovery rate >85%. The recovered phosphorus product is modified with hydroxyapatite to prepare a slow-release soil conditioner.

[0065] S7: The integrated biological filter tower (sulfur oxidation / nitrifying bacteria) and activated carbon adsorption device treat pyrolysis tail gas. It uses amino-functionalized silica gel to capture CO and convert it into bicarbonate, achieving carbon sequestration and odor removal rate >95%.

[0066] S8: Deploy a digital twin system to monitor data in real time through online sensors and combine it with an LSTM neural network to predict the optimal process parameters (such as ultrasonic intensity and pyrolysis temperature) and dynamically adjust the equipment's operating status.

[0067] S9: Biochar is used for deep phosphorus removal in sewage treatment plants and slow-release phosphate fertilizer to support municipal greening. The system effluent meets the Class A standard of the "Discharge Standard of Pollutants for Urban Wastewater Treatment Plants" (GB 18918-2002). The carbon emission reduction of the whole process is >1.2 kg CO equivalent / ton of sludge.

[0068] In step S1, concentrated sludge from a wastewater treatment plant, with an initial moisture content controlled at 95%–97%, is first treated in a high-frequency ultrasonic reactor at a frequency of 20–40 kHz. The ultrasonic power density is set to 0.5 watts per milliliter, and the treatment time is 30 minutes. The sludge temperature is maintained below 35 degrees Celsius to prevent pyrolysis of organic matter. After treatment, 5 grams of calcium peroxide powder are added per liter of sludge, and the mixture is stirred at 200 rpm for 20 minutes to ensure uniform dispersion of calcium peroxide and release of active oxygen, simultaneously completing cell wall disruption, heavy metal passivation, and pathogen inactivation. The dissolved chemical oxygen demand (SCOD) of the pretreated sludge is increased to more than 2.3 times that of the original sludge, and the volatile solids (VS) degradation rate is less than 8%.

[0069] In step S2, the biochar-supported nanomaterials include: 70 parts by weight of sludge-based biochar, 15 parts by weight of polydopamine-coated nano-zero-valent iron, 10 parts by weight of conductive polyaniline, 8 parts by weight of superparamagnetic Fe3O4, 5 parts by weight of diammonium hydrogen phosphate, 3 parts by weight of calcium carbonate, and 2 parts by weight of KOH activator.

[0070] The preparation method of biochar-supported nanomaterials includes: firstly, dewatered sludge from a wastewater treatment plant is taken and subjected to a stepped pyrolysis process, followed by pre-carbonization at 300℃ for 30 minutes and activation at 600℃. During the activation stage, KOH is used for impregnation at a mass ratio of 1:2, and the mixture is kept at this temperature for 1 hour under nitrogen protection. Subsequently, ash is removed by acid washing with 0.1M HCl, followed by washing with deionized water, vacuum drying, and grinding to 200 mesh to obtain sludge-based biochar. Next, the biochar is soaked in 0.5M FeSO4 solution at a solid-liquid ratio of 1:10, ultrasonically dispersed for 30 minutes, and then 0.5M FeSO4 solution is added dropwise. NaBH4 solution was used to generate nano-zero valent iron by controlling the molar ratio of Fe2+ to BH4- at 1:2 under nitrogen protection for 2 hours. Then, aniline monomer with a mass ratio of 1:5 to biochar was added, and in-situ polymerization was carried out using ammonium persulfate as an initiator to form a polyaniline conductive coating layer. Finally, FeCl2·4H2O and FeCl3·6H2O were dissolved in a 1:2 molar ratio by co-precipitation, and ammonia was added dropwise to adjust the pH to 10. Fe3O4 magnetic particles were prepared by stirring at 60°C for 1 hour. The particles were then separated and loaded onto the surface of biochar by magnetic field separation, and then mixed with diammonium hydrogen phosphate and calcium carbonate by ball milling at 300 rpm for 2 hours. Finally, the mixture was pressed into tablets and granulated to obtain the finished biochar-supported nanomaterials with a particle size of 2-3 mm.

[0071] In step S3, the anaerobic digestion residue is dewatered to 80% moisture content using a plate and frame filter press, and then fed into a microwave-assisted hot hydrolysis reactor. The reaction conditions are set to a microwave power of 800 watts, a heating rate of 10 degrees Celsius per minute, a target temperature of 160 degrees Celsius maintained for 30 minutes, and a reaction pressure stabilized at 6 bar via an automatic pressure relief valve. The hydrolyzed material is discharged via a screw conveyor, and polyaluminum chloride (PAC) is added as a conditioner at a dosage of 5% of the dry sludge mass. After a second dewatering process using a belt filter press, the moisture content is reduced to below 60%, and the sludge resistivity is reduced to 1.0 × 10^12 m / kg. Simultaneously recovered volatile fatty acids are collected via a condenser at a concentration of 12,000 mg / L and directly reused as a carbon source for denitrification in the wastewater treatment plant.

[0072] In step S4, the dewatered sludge is transported to a double-layered solar greenhouse with 92% light transmittance. The top of the greenhouse is covered with a phase change thermal storage material (paraffin-expanded graphite composite material, phase change temperature 45 degrees Celsius), and the bottom is laid with a breathable and impermeable membrane. During the day, solar radiation is used to raise the temperature to 50-60 degrees Celsius, and at night, a heat pump is activated to maintain the temperature at 40 degrees Celsius. Continuous drying for 72 hours reduces the sludge moisture content to 65%. Subsequently, a hydrophobic metal-organic framework (MOF-303) adsorption bed is used for deep dewatering. The MOF material packing density is 200 kg per cubic meter, the adsorption cycle is 6 hours, and the final sludge moisture content is reduced to 55%, with a unit energy consumption of 0.6 kWh per ton of water evaporation.

[0073] In step S5, the dewatered sludge enters a rotary pyrolysis furnace and is heated in three stages under a nitrogen atmosphere: the first stage heats up to 300 degrees Celsius at a rate of 15 degrees Celsius per minute, with a residence time of 30 minutes to achieve initial cracking of organic matter; the second stage heats up to 500 degrees Celsius, with a residence time of 45 minutes to complete secondary cracking of tar; the third stage heats up to 700 degrees Celsius and holds at that temperature for 60 minutes to generate biochar with a specific surface area greater than 500 square meters per gram. The pyrolysis gas, after dust removal by a cyclone separator, enters a catalytic reforming tower, where it is reformed into syngas (H+CO ratio > 70%) at 850 degrees Celsius using a nickel-based catalyst. This syngas is then reused for combustion and heating in the pyrolysis furnace, achieving an energy self-sufficiency rate of 85%.

[0074] In step S6, the pyrolysis ash is pulverized to 100 mesh using a ball mill. A 1 mol / L sulfuric acid solution is added at a solid-liquid ratio of 1:10, and the mixture is stirred and leached at 80°C for 2 hours, achieving a phosphorus leaching rate exceeding 90%. After adjusting the pH of the leachate to 9.0, biochar-loaded magnesium chloride (MgCl₂·6H₂O to biochar mass ratio 1:5) is added, reacting to form struvite crystals. These crystals are then centrifuged, washed with pure water, and yielded magnesium ammonium phosphate with a purity >95%. Further calcination at 450°C for 2 hours converts it into hydroxyapatite slow-release fertilizer, with a phosphorus dissolution rate controlled below 5% within 24 hours.

[0075] In step S7, the pyrolysis tail gas, after passing through a bag filter, enters a two-stage biological filter tower: the first stage is filled with sulfur-oxidizing bacteria biological packing material, with an empty tower residence time of 40 seconds, achieving a hydrogen sulfide removal efficiency >98%; the second stage is filled with nitrifying bacteria biofilm, with the spray liquid pH controlled at 7.5-8.0, achieving an ammonia nitrogen removal rate >90%. The purified tail gas is then passed into an amino-functionalized silica gel adsorption tower, with an adsorbent bulk density of 600 kg / m³, selectively capturing carbon dioxide at 50°C. After adsorption saturation, it is desorbed by steam at 120°C, achieving a carbon dioxide purity >99%. The gas is then pressurized to 30 bar and liquefied for storage.

[0076] In step S8, a digital twin system is deployed to collect real-time data from 12 types of sensors, including sludge flow rate, temperature, pH, ORP, and volatile fatty acids, updating the database every 5 seconds. A multivariate prediction model is established using a Long Short-Term Memory (LSTM) neural network, with 32 neurons in the input layer, 64 nodes in the hidden layer, and the output layer dynamically optimizing 18 process parameters such as ultrasonic power, pyrolysis temperature, and MOF adsorption cycle. The system generates a global optimization scheme every 24 hours using a reinforcement learning algorithm, achieving equipment control response time of less than 1 second and reducing overall energy consumption by 12%.

[0077] In step S9, the prepared biochar is added at a ratio of 20 grams per ton of wastewater to the advanced treatment unit after the secondary sedimentation tank, achieving a total phosphorus adsorption capacity of 35 mg / g, replacing 80% of the traditional polyferric sulfate reagent usage. Hydroxyapatite slow-release fertilizer is evenly spread using municipal greening fertilizer trucks, with an annual application rate of 5 kg per acre, increasing the available phosphorus content in the soil by 2.3 times. The final effluent quality of the system meets the requirements of chemical oxygen demand (COD) ≤ 30 mg / L and total phosphorus ≤ 0.3 mg / L. The carbon footprint of the entire sludge treatment process is calculated to reduce emissions by 1.5 kg of carbon dioxide equivalent per ton of dry sludge.

[0078] From the above, we can conclude that:

[0079] This invention achieves a dual breakthrough in environmental and economic benefits through multi-level synergy and resource closed-loop design. The synergistic effect of biochar-supported nanomaterials significantly improves the decomposition efficiency of organic matter. Its unique conductive network structure accelerates electron transfer during anaerobic digestion, enabling the methane generation rate to break through the bottleneck of traditional processes, while effectively inhibiting the generation of malodorous byproducts such as hydrogen sulfide. The superparamagnetic component endows the material with highly efficient recovery characteristics. Combined with a slow-release nutrient system, it significantly enhances microbial metabolic activity while reducing dependence on chemical agents, ensuring the stabilization of heavy metals and the inactivation of pathogens. The energy and material recycling design of each stage of the process converts sludge pyrolysis gas into a heat source for the system's own use, forming an internal energy circulation link and significantly reducing the demand for external energy input.

[0080] In this invention, a biochar-based deep phosphorus removal unit replaces traditional chemical agents, reducing the risk of secondary pollution. The recovered phosphorus resources are modified and transformed into a slow-release soil conditioner, simultaneously addressing the dual challenges of phosphorus removal costs in wastewater treatment plants and phosphorus deficiency in urban greening. Solar-coupled adsorption dehydration technology overcomes the high energy consumption limitations of traditional thermal drying, and combined with an intelligent control system, achieves refined management of the dehydration process. The final product chain encompasses various high-value products such as energy gases, carbon-based materials, and slow-release fertilizers, forming a closed-loop model of "treatment-reuse-feedback." This not only reduces the overall cost of sludge disposal but also extends into derivative values ​​such as ecological restoration and carbon sequestration enhancement, endowing wastewater treatment plants with sustainable operational capabilities.

[0081] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes the element.

[0082] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sludge treatment process for wastewater treatment plants, characterized in that: The processing technology includes the following steps: S1: Civil engineering reinforced concrete ultrasonic tank body, pre-embedded galvanized steel pipe conduit, installation of 316L stainless steel vibrating plate base, and integrated CPVC calcium peroxide dosing pipeline system on the tank top. S2: Construct the civil engineering structure of a two-phase anaerobic reactor with an internal biochar conductive dielectric layer; S3: Construct a microwave hydrolysis reaction tank and pre-bury the supporting volatile fatty acid recovery pipeline; S4: Civil engineering solar greenhouse drying workshop, with MOFs material adsorption layer embedded in the wall surface; S5: Casting the structure of the oxygen-deficient pyrolysis kiln, and matching the pyrolysis gas catalytic reforming and reuse pipeline network; S6: Construct an acid leaching reaction tank and crystallization device, using a biochar magnesium source carrier structure; S7: Civil engineering biological filter tower base, with activated carbon adsorption unit and CO2 capture pipeline installed; S8: Embed a network of sensors for monitoring process parameters and deploy a digital twin control system; S9: Implement full-chain civil engineering renovation: secondary sedimentation tank with embedded biochar filter interlayer: stainless steel grid anchored concrete; rain garden with layered backfilling of biochar planting soil; geotextile wrapped with biochar adsorption layer at the bottom of municipal pipe trench, and installation of detachable inspection well structure. In step S1, concentrated sludge from a wastewater treatment plant is taken, with an initial moisture content controlled at 95% to 97%. It is first treated by a high-frequency ultrasonic reactor with a frequency of 20 kHz to 40 kHz, an ultrasonic power density of 0.5 watts per milliliter, and a continuous treatment time of 30 minutes. The sludge temperature is maintained below 35 degrees Celsius to prevent the pyrolysis of organic matter. In step S2, the biochar-supported nanomaterials include: 60-70 parts by weight of sludge-based biochar, 10-15 parts by weight of polydopamine-coated nano-zero-valent iron, 8-10 parts by weight of conductive polyaniline, 5-8 parts by weight of superparamagnetic Fe3O4, 3-5 parts by weight of diammonium hydrogen phosphate, 2-3 parts by weight of calcium carbonate, and 1-2 parts by weight of KOH activator. In step S3, the residue after anaerobic digestion is dehydrated to a moisture content of 80% by a plate and frame filter press, and then enters a microwave-assisted hot water hydrolysis reactor. The reaction conditions are set as follows: microwave power of 800 watts, heating rate of 10 degrees Celsius per minute, target temperature of 160 degrees Celsius and maintained for 30 minutes, and reaction pressure is stabilized at 6 bar by an automatic pressure relief valve. In step S4, the dewatered sludge is transported to a double-layered solar greenhouse with a light transmittance of 92%. The top of the greenhouse is covered with phase change heat storage material, and the bottom is laid with a breathable and impermeable membrane. During the day, the temperature is raised to 50-60 degrees Celsius using solar radiation.

2. The sludge treatment process for a wastewater treatment plant as described in claim 1, characterized in that: In step S5, the dewatered sludge enters a rotary pyrolysis furnace and is heated in three stages under a nitrogen atmosphere: in the first stage, the temperature is increased to 300 degrees Celsius at a rate of 15 degrees Celsius per minute and held for 30 minutes to achieve the initial cracking of organic matter; in the second stage, the temperature is increased to 500 degrees Celsius and held for 45 minutes to complete the secondary cracking of tar; in the third stage, the temperature is increased to 700 degrees Celsius and held for 60 minutes.

3. The sludge treatment process for a wastewater treatment plant as described in claim 1, characterized in that: In step S6, the pyrolysis ash is pulverized to 100 mesh using a ball mill, and a sulfuric acid solution with a concentration of 1 mol / L is added at a solid-liquid ratio of 1:

10. The mixture is then stirred and leached at 80 degrees Celsius for 2 hours, resulting in a phosphorus leaching rate of over 90%. After adjusting the pH of the leachate to 9.0, magnesium chloride loaded with biochar is added, and struvite crystals are generated. After centrifugation and washing with pure water, magnesium ammonium phosphate with a purity >95% is obtained. The phosphate is then further calcined at 450 degrees Celsius for 2 hours.

4. The sludge treatment process for a wastewater treatment plant as described in claim 1, characterized in that: In step S7, the pyrolysis tail gas enters a two-stage biological filter tower after passing through a bag filter: the first stage is filled with sulfur-oxidizing bacteria biological packing material, with an empty tower residence time of 40 seconds and a hydrogen sulfide removal efficiency of >98%; the second stage is filled with nitrifying bacteria biofilm, with the pH of the spray liquid controlled at 7.5-8.0 and an ammonia nitrogen removal rate of >90%.

5. The sludge treatment process for a wastewater treatment plant as described in claim 1, characterized in that: In step S8, a digital twin system is deployed to collect real-time data from 12 types of sensors, including sludge flow, temperature, pH, ORP, and volatile fatty acids, and the database is updated every 5 seconds.

6. The sludge treatment process for a wastewater treatment plant as described in claim 1, characterized in that: In step S9, the prepared biochar is added at a ratio of 20 grams per ton of wastewater to the deep treatment unit after the secondary sedimentation tank, with a total phosphorus adsorption capacity of 35 mg / g, replacing 80% of the traditional polyferric sulfate reagent.

Citation Information

Patent Citations

  • Method for strengthening anaerobic digestion of sludge by utilizing pre-alcoholization of kitchen waste

    CN112047590A

  • Soil improvement process for coupling sludge pyrolysis and carbonization with sludge treatment

    CN115231790A